Descentralização e financiamento dos serviços de saúde no Brasil - Tobar, Federico (1995)
This paper analyses the financiai restraints on the decentralization of health services. In part One we go through different types of decentralization and their economic features. And in Part Two the special case of the brazilian experience is evaluated.